MEASURING AND TESTING NDB EQUIPMENT IN SPECIFIC CONDITIONS (Perner's Contacts, 2017)
This paper describes the consistent preview of the measuring and testing Non Directional Beacon with using flying laboratory Aerolab 1 at University of Zilina. The ADF/NDB navigation system is one of the oldest air navigation systems still in use today. It works from the most simple radio navigation concept: a ground-based radio transmitter (the NDB) sends an omnidirectional signal that an aircraft loop antenna receives.
Keywords: Radio-navigation; Aircraft; Non directional Beacon